Contagion and the state in Europe, 1830-1930 - Baldwin, Peter, 1956- (Cambridge University Press, 1999)
"This book explains the historical reasons for the divergence in public health policies in Britain, France, Germany and Sweden, and the spectrum of responses to the threat of contagious diseases such as cholera, smallpox, and syphilis." "In particular the book examines the link between politics and prevention."--Jacket